Hemodynamic stratification using transthoracic echocardiography in patients with ST segment elevation acute myocardial infarction - Hidalgo Rosales, Jorge (2017)
Objective: To evaluate the feasibility of performing a hemodynamic stratification in patients with ST segment elevation acute myocardial infarction using transthoracic echocardiography. Materials and methods: A descriptive, prospective and cross-sectional study that included 30 patients in sinus rhythm with ST segment elevation acute myocardial infarction, admitted to the coronary care unit of Hospital Edgardo Rebagliati Martins. Cardiac output, left ventricle filling pressure, systemic vascular resistance and pulmonary vascular resistance were estimated. Results: The mean age was 67 ± 10.6 years old, with male predominance (86.7%). The estimation of cardiac output and left ventricle filling pressure was possible in 100% of the individuals. The systemic vascular resistance and pulmonary vascular resistance could be estimated in 29 (96.6%) and 28 (93.3%) patients, respectively. The hemodynamic stratification was as follows: stage I (normal): 18 patients (60%), stage II (congestive): 6 patients (20%), stage III (hypovolemia, RV infarction): 5 patients (16.7%) and stage IV (shock): 1 patient (3.3%). Conclusions: It is concluded that a transthoracic echocardiographic hemodynamic stratification may be performed in the studied population.